Evaluation of the partitioned mechanical properties and the hall-petch relationship of cast aluminum alloy cylinder head - Yan, Kangjie; Huang, Weiqing; Zuo, Zhengxing; Liu, Jinxiang; Ren, Peirong; Hu, Dingyun; Zhao, Chengzhang (MATEC web of conferences, 2022)
In view of the non-uniform distribution of mechanical properties of cast aluminum alloy cylinder head, the mechanical properties evaluation and microstructure heterogeneity of cylinder head were studied. The results showed that the head plate position of the cylinder head has the best mechanical properties and microstructure characterization, followed by the floor plate and the thick partition plate. The mechanical properties of the floor plate position attenuate with increasing temperature. From 23°C to 300°C, the tensile strength and yield strength decrease in the same range, but the break elongation changes most obviously. The mechanical properties and microstructure characterization of cylinder head in-situ sampling satisfy the Hall-Petch relationship. If the required ultimate tensile strength is not less than 255MPa, the upper threshold of the grain size, by considering the error limit of the Hall-Petch relationship, is 603.4μm, and the upper threshold of secondary dendrite arm spacing is 69.1μm. Meanwhile, established the relationship between hardness and yield strength, the average error of the nonlinear model is 4.35%. The prediction accuracy of the nonlinear model is sufficient to meet the actual needs of the engineering.